Diagnosis of Thyroid Malignancy using Chemical Elements of Nodular Tissue determined by Nuclear Analytical Methods - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2022)
Background: Thyroid benign (TBN) and malignant (TMN) nodules are a common thyroid lesion. The differentiation of TMN often remains a clinical challenge and further improvements of TMN diagnostic accuracy are warranted. Objectives:The aim of present study was to evaluate possibilities of using differences in chemical elements (ChEs) contents in nodular tissue for diagnosis of thyroid malignancy. Methods: Contents of ChEs such as silver (Ag), calcium (Ca), chlorine (Cl), cobalt (Co), chromium (Cr), cooper (Cu), iron (Fe), mercury (Hg), iodine (I), potassium (K), magnesium (Mg), manganese (Mn), sodium (Na), rubidium (Rb), ammonium (Sb), scandium (Sc), selenium (Se), strontium (Sr), and zinc (Zn) were prospectively evaluated in “normal” thyroid (NT) of 105 individuals as well as in nodular tissue of thyroids with TBN (79 patients) and to TMN (41 patients). Measurements were performed using a combination of non-destructive methods X-ray fluorescence and instrumental neutron activation analysis with high resolution spectrometry of short- and long-lived radionuclides. Results: It was observed that in TMN tissue the mean mass fraction of I was lower while the mean mass fractions of K, Mg, and Rb were higher than in NT and TBN tissue. It was demonstrated that I content is nodular tissue is the most informative parameter for the diagnosis of thyroid malignancy. It was found that “Sensitivity”, “Specificity” and “Accuracy” of TMN identification using the I level in the needle biopsy of affected thyroid tissue was significantly higher than that using US examination and cytological test of fine needle aspiration biopsy. Conclusions: It was concluded that determination of the I level in a needle biopsy of TNs using non-destructive instrumental analytical method is a fast, reliable, and very informative diagnostic tool that can be successfully used as an additional test of thyroid malignancy identification.